Data for: Comparative analysis of gut microbiome alterations in early- and late-onset preeclampsia: a case control study - Meijer, Sofie; Hansson, Stefan (Region Skåne, 2026)
The data set contains demographic data from 37 pregnant women in the third trimester (21 normal pregnancies, 16 preeclampsia), and includes variables such as age, parity, BMI, pregnancy outcome, measurement of calprotectin in blood and stool, and survey answers regarding gastrointestinal symptoms.

Datafilen innehåller demografisk data från 37 gravida kvinnor i tredje trimestern (21 normala graviditeter, 16 preeklampsi), och inkluderar variabler såsom ålder, paritet, BMI, graviditetsutfall, mätning av calprotectin i blod och avföring samt enkätsvar gällande symptom från tarmen.
Data for: Comparative analysis of gut microbiome alterations in early- and late-onset preeclampsia: a case control study
Keywords: Pre-eclampsia; Preeklampsi; Gastrointestinal Microbiome; Tarmflora; Gynaecology, Obstetrics and Reproductive Medicine; Gynekologi, obstetrik och reproduktionsmedicin